The joy of science : seven principles for scientists seeking happiness, harmony, and success - Snieder, Roel, 1958-; Schneider, Jennifer J. (Cambridge : Cambridge University Press, 2016)
We live in an age where working in science or engineering offers tremendous professional opportunities - the pace of scientific development is truly breathtaking. Yet many researchers struggle with the pressures of the fast-paced academic workplace, and struggle to harmonize their work and personal lives. The result can be burnout, exhaustion, and stress on a personal level, and difficulty in recruiting and retaining talented, diverse people to science and engineering. This book, written for graduate students and researchers at all stages of their careers, aims to help scientists by identifying and questioning the core beliefs that drive a culture of overwork, and provides real-world examples and exercises for those wishing to do things differently. Written in a lively narrative style, and including interview excerpts from practicing scientists, social scientists, and engineers, this book serves as a guide for those seeking to practice the seven traits of the joyful scientist.
Harmony -- Courage -- Vision -- Curiosity -- Listening -- Compassion -- Integrity.
Title from publisher's bibliographic system (viewed on 06 Jun 2016).
Keywords: Creative ability in science; Science -- Vocational guidance; Science -- Psychological aspects; Engineering -- Vocational guidance; Engineering -- Psychological aspects; Job satisfaction